Dyslipidemia: what it is, how to identify, causes and treatment. - Bezerra, Clarisse (Brazilian Journal of Implantology and Health Sciences, 2023)
Dyslipidemia is a disease characterized by abnormalities in blood lipid levels, mainly total cholesterol and triglycerides. Other changes include low high-density lipoprotein cholesterol (HDL-C) and high levels of low-density lipoprotein cholesterol (LDL-C)